In vitro evaluation of Lactiplantibacillus plantarum HOKKAIDO strain, effective lactic acid bacteria for calf diarrhea - Ikehata, Mari; Konnai, Satoru; Okagawa, Tomohiro; Abe, Kentaro; Honma, Mitsuru; Kitamura, Toru; Maekawa, Naoya; Suzuki, Yasuhiko; Murata, Shiro; Ohashi, Kazuhiko (Frontiers in Veterinary Science, 2023)
Calf diarrhea adversely affects growth and sometimes results in mortality, leading to severe economic losses to the cattle industry. Antibiotics are useful in the treatment against bacterial diarrhea, but not against viral, protozoan, and antibiotic-resistant bacterial diarrhea. Therefore, there are growing requirements for a novel control method for calf diarrhea. Probiotics have been considered promising candidates for preventive and supportive therapy for calf diarrhea for many years. A recent study has revealed that Lactiplantibacillus plantarum HOKKAIDO strain (Lp-HKD) reduces intestinal pathology and the severity of diarrhea in bovine rotavirus (BRV)-infected calves. Lp-HKD is known to enhance the function of human immune cells and expected to be used as probiotics for humans. Therefore, it is hypothesized that Lp-HKD modulates antiviral immune response in cattle and provide the clinical benefits in BRV-infected calves. However, the detailed mechanism of Lp-HKD-induced immunomodulation remains unknown. Thus, this study aimed to elucidate the immunomodulatory and antiviral effects of Lp-HKD in cattle. Cultivation assay of bovine peripheral blood mononuclear cells (PBMCs) showed that live and heat-killed Lp-HKD stimulates the production of interleukin-1β (IL-1β), IL-6, IL-10, and interferon-γ (IFN-γ) from PBMCs. Stimulation by heat-killed Lp-HKD yielded stronger cytokine production than stimulation by the live Lp-HKD. Additionally, CD14+ monocytes were identified as major producers of IL-1β, IL-6, and IL-10 under Lp-HKD stimulation; however, IFN-γ was mainly produced from immune cells other than CD14+ monocytes. Depletion of CD14+ monocytes from the PBMCs cultivation strongly decreased cytokine production induced by heat-killed Lp-HKD. The inhibition of toll-like receptor (TLR) 2/4 signaling decreased IL-1β and IL-6 production induced by live Lp-HKD and IL-1β, IL-6, and IFN-γ production induced by heat-killed Lp-HKD. Furthermore, live or heat-killed Lp-HKD also activated T cells and their production of IFN-γ and tumor necrosis factor-α. Then, culture supernatants of bovine PBMCs treated with heat-killed Lp-HKD demonstrated antiviral effects against BRV in vitro. In conclusion, this study demonstrated that Lp-HKD activates the functions of bovine immune cells via TLR2/4 signaling and exerts an antiviral effect against BRV through the induction of antiviral cytokines. Lp-HKD could be useful for the prevention and treatment of calf diarrhea through its immune activating effect.